HUBUNGAN PENGETAHUAN DAN SIKAP TERHADAP KESIAPSIAGAAN DALAM PENANGGULANGAN KEBAKARAN PADA MASYARAKAT DI RW 010 KELURAHAN WARAKAS TANJUNG PRIOK - Shania Hasina Sidiki (2021)
During early January to July 14, 2021 there are 770 fires occurred with an estimated loss of Rp 104.570.800. The community as the main part of the first to bear the impact of fires must have preparedness in the face of fire hazards. The purpose of this study was to analyze the relationship between knowledge and attitudes towards fire preparedness in the community at RW 010 Kelurahan Warakas Tanjung Priok. The research method used in this research is quantitative with analytical descriptive design, using a cross sectional approach. The population in this study was the community of RW 010 Kelurahan Warakas Tanjung Priok with a total sample of 292 families. The sampling technique used in this study was accidental sampling. Data collected using a questionnaire. This study uses the Chi square test. The results of this study indicate that there is a relationship between knowledge and fire preparedness with a p-value of 0.008 (p<0.05), and there is a relationship between attitude and fire preparedness with a p-value of 0.000 (p<0, 05). The community needs to increase knowledge and attitudes about fire preparedness so that when a fire occurs, the community already understands the actions that must taken.